Estudo de egressos de medicina e a ecologia médica no cenário pandêmico da Covid-19 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The Covid-19 pandemic has revealed the lack of knowledge about a virus that has caused a global collapse since March 2020, forcing structural changes in health systems in search of prevention and care for the population, raising questions about its causes. One consequence was the early graduation of health professionals, in order to incorporate them into the front lines in the fight against Covid-19. In this scenario, Medical Ecology (ME) is the science that studies diseases and the relationship between human beings and the environment and their imbalances, with a view to restoring the balance between man and nature. In this sense, this research analyzed the training of medical graduates who graduated early from the State University of Pará (UEPA), Medical Ecology and the possible impacts/losses in the face of the Covid-19 scenario. As specific objectives, we sought to: outline the profile of these medical graduates from UEPA (2020-2022) considering their practical insertion in the face of the Covid-19 pandemic ; to analyze the unified curriculum of the UEPA medical course and its contribution to a more humanized education; to understand EM and its principles from the perception of graduates, professors and coordinators of the medical course at the UEPA campuses : Belém, Santarém and Marabá; and to evaluate the possible impacts/losses resulting from early graduation in the training process of these graduates and in their professional practice in facing the pandemic situation . Bibliographic, documentary and empirical research was carried out, with a sample of 49 participants based on semi-structured interviews with 04 coordinators and 08 professors, and the online questionnaire applied to 37 graduates who graduated early (2020, 2021 and 2022). The research has a transdisciplinary approach, using data The qualitative and quantitative studies , adopting content analysis and the triangulation method, were approved by the Research Ethics Committee of the Federal University of Western Pará. As for the results, it was proven that the object of study was unprecedented, after a systematic review of the literature, given the absence of publications. The profile of the physicians graduated from UEPA is formed, the majority composed of women, young, single and active in the fight against Covid-19, working in the state of Pará. However, the search for continuing education in medical residencies was evidenced, with the professional practice scenarios being basic health units, hospitals and clinics, in the public and private services. Regarding EM, it was found that the participants were unfamiliar with the term, but applied its principles within the modules. The course favored a humanized medical training and the modules that contributed the most were Medical Humanities, GIESC and Internship in Internal Medicine. However, the majority said “Yes” to the occurrence of impacts on internships, with emphasis on the absence of the modules: Mental Health and Public Health. The coordinators and teachers who worked in the context studied also indicated the reduction of the field of practice. Regarding the losses due to the anticipation, there is a certain balance between the answers; despite this, the objective proposed by Ordinance 374, of the Ministry of Education, was achieved with the increase in professionals in the fight against Covid-19
Keywords: Formação médica; Processo saúde-doença; Humanização; Ciências ambientais; Amazônia; Ecologia Médica; CNPQ:: CIENCIAS AMBIENTAIS; Gestão do conhecimento e inovação para o desenvolvimento sustentável.